Development of Psychoeducational Guidelines Containing Madurese Values to Prevent Bullying in Boarding Schools - Sadikin, Ahmad Ali; Ramli, M.; Rahman, Diniy Hidayatur; Arip, Nur Aziz Shah Bin Mohamed; Saputra, Mega Aris (citeus, 2025)
Bullying is a deeply concerning issue within the education sector in Indonesia, posing serious threats to the well-being of students. The impacts of bullying can be severe, leading to fatal outcomes for victims or causing lasting psychological effects for survivors. A particular area of concern is bullying in boarding schools, where students are frequently involved in social interactions. This research aims to develop a psychoeducational program incorporating Madurese values for use in boarding schools. The study employed a research and development methodology following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research included content experts, cultural experts, media experts, and potential users, specifically guidance and counseling teachers, with data collected using a product acceptability scale. The collected data were analyzed using the inter-rater agreement model. The research and development process were conducted to achieve both theoretical and practical acceptability of the product. The results indicated that the product was highly acceptable to content experts, cultural experts, media experts, and potential users, demonstrating high accuracy, usefulness, attractiveness, and ease of use across all evaluated aspects.